Molluscum contagiosum/Condylomata acuminata. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2005)
Both molluscum contagiosum and condylomata acuminata are expression of a virus-induced cytopathogenic effect on the epidermal keratinocytes. In both cases the virus is responsible for proliferation and thus thickening of the epidermis (Fig. 5, 6). Although the clinical features of the two infections are rather different in their typical sites (Fig. 1, 2) and easily differentiable from each other, in the groins, where they can be both present (Fig. 3, 4), their differentiation is more difficult and mainly based on their pathological findings (Fig. 5, 6).